Cardiac care in critically Ill neurological patients - Brachmann, Johannes; Moore, Laurie; Schuster, Hans-Peter (Neurocritical care, 1994)
The upper limits of normal for systolic and diastolic blood pressures are 140 and 90 mmHg, respectively. Repeated measured values above 150 mmHg systolic or 90 mmHg diastolic must be considered hypertension. Chronic hypertension is implicated in ischemic heart disease, atherosclerotic vascular disease, renal failure, and stroke. Although the most common form of hypertension, essential hypertension, is of unknown etiology, secondary causes of hypertension include renal and renovascular disease, endocrine disorders (Cushing’s syndrome, Conn’s syndrome, pheochromocytoma, or carcinoid), obesity, and pregnancy. A thorough evaluation of hypertensive patients is indicated. An overview is given in Table 1.